THE EFFECTIVENESS OF HAND MASSAGE THERAPY IN REDUCING PAIN INTENSITY AMONG PATIENTS WITH POST-LAPARATOMY SURGERY - Wiwin Silpia; Nurhayati Nurhayati; Henni Febriawati (Jurnal Vokasi Keperawatan (JVK), 2021)
The incidence of laparotomy increases gradually year by year. Based on a preliminary survey that was conducted in a public hospital in Bengkulu, it was found that there were increasing cases of laparotomy surgery within the last three years. One of the main issues reported by patients with post-laparotomy surgery is acute pain in the area of incision surgery. The aim of this study was to determine the effectiveness of hand massage therapy in reducing acute pain among post-laparotomy surgery patients. This research was a quasi-experimental study with pre-test and post-test groups. The results of this study found that the respondent's ages ranged from 20 to 40 years old (53.3%) and most of them were male (60%). A total of 53.3% of respondents experienced severe pain after surgery, then the pain intensity decreased to mild pain by 86.7% after being given hand massage therapy. The implication of this study was expected to be a reference for nurses in dealing with acute pain in post-surgical patients.